Body mass index and all cause mortality in HUNT and UK Biobank studies: linear and non-linear mendelian randomisation analyses. (26th March 2019) - Sun, Yi-Qian; Burgess, Stephen; Staley, James R; Wood, Angela M; Bell, Steven; Kaptoge, Stephen K; Guo, Qi; Bolton, Thomas R; Mason, Amy M; Butterworth, Adam S; Di Angelantonio, Emanuele; Vie, Gunnhild Å; et al.
Abstract: Objective: To investigate the shape of the causal relation between body mass index (BMI) and mortality. Design: Linear and non-linear mendelian randomisation analyses. Setting: Nord-Trøndelag Health (HUNT) Study (Norway) and UK Biobank (United Kingdom). Participants: Middle to early late aged participants of European descent: 56 150 from the HUNT Study and 366 385 from UK Biobank. Main outcome measures: All cause and cause specific (cardiovascular, cancer, and non-cardiovascular non-cancer) mortality. Results: 12 015 and 10 344 participants died during a median of 18.5 and 7.0 years of follow-up in the HUNT Study and UK Biobank, respectively. Linear mendelian randomisation analyses indicated an overall positive association between genetically predicted BMI and the risk of all cause mortality. An increase of 1 unit in genetically predicted BMI led to a 5% (95% confidence interval 1% to 8%) higher risk of mortality in overweight participants (BMI 25.0-29.9) and a 9% (4% to 14%) higher risk of mortality in obese participants (BMI ≥30.0) but a 34% (16% to 48%) lower risk in underweight (BMI <18.5) and a 14% (−1% to 27%) lower risk in low normal weight participants (BMI 18.5-19.9). Non-linear mendelian randomisation indicated a J shaped relation between genetically predicted BMI and the risk of all cause mortality, with the lowest risk at a BMI of around 22-25 for the overall sample. Subgroup analyses by smoking status, however, suggested an always-increasing relation of BMI with mortality in never smokers and a J shaped relation in ever smokers. Conclusions: The previously observed J shaped relation between BMI and risk of all cause mortality appears to have a causal basis, but subgroup analyses by smoking status revealed that the BMI-mortality relation is likely comprised of at least two distinct curves, rather than one J shaped relation. An increased risk of mortality for being underweight was only evident in ever smokers.